THE ROLE OF INTERNET SPACE IN FACILITATING AUTONOMOUS LEARNING IN ENGLISH TEACHING (Лучшие интеллектуальные исследования, 2024)
This study explores the role of internet space in facilitating autonomous learning in English language teaching focusing on three key gaps in current educational practices. First, it addresses the gap in access to diverse, personalized learning resources, highlighting how the internet provides a wealth of materials such as language learning apps, online courses, and authentic media that can cater to individual learning needs and preferences